Penggunaan Model Card Sort di kelas V SDN 16 Payakumbuh Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Pembelajaran Tematik Terpadu - Muhammad Farhan; Zuryanty Zuryanty (Innovative: Journal Of Social Science Research, 2023)
The basis of this research is the fact that low learning outcomes are the result of inadequate learning implementation. This research is expected to be able to describe the expansion of learning outcomes using the Card Sort model. This research was carried out at SDN 16 Payakumbuh with the research subjects being educators and fifth grade students. The stages of planning, implementing, observing, and reflecting on this research were carried out over two cycles. The results of the RPP aspect in the first cycle obtained 80.56%, increasing in the second cycle 94.44%. Observation of the educator aspects of cycle I was 83.34% and cycle II increased by 95.83%. Observation of student aspects in cycle I was 81.25%, an increase of 91.66% in cycle II. Student learning outcomes in cycle I 77.03 and cycle II 84.67. Thus the Card Sort model can improve learning outcomes.